Automatic impulse response for experimental modal analysis on running harmonics condition / A. Jannifar - A. , Jannifar (2018)
A machine that undergoes resonance will demonstrate high vibration level and often leads to mechanical problems such as a worn rotating element, looseness and crack propagation. However, within the scope of Condition Based Maintenance (CBM), the vibration analysis technique typically employed within the troubleshooting protocols unable to resolutely diagnose resonance as the root of such problems since the conclusions are made based on the anomalies of signal captured representing the faults. Thus, a measurement system that can resolve the resonance frequency of machines is indispensable. Experimental Modal Analysis (EMA) is a well-known technique used to extract the dynamic characteristics (resonance related parameters) of structure under non-operational condition. Nevertheless, the cost of shutdown of operating machines is significantly high especially in power generation industries. Therefore, the need to conduct EMA in operational condition has motivated the present research. In operating condition, harmonic excitation signal produced by the running cyclic machine may contaminate the input and output signals. Therefore, this disturbance must be filtered to attain clean output response signal that is purely from the input force. In this study, a time based block-averaging algorithm was proposed to eliminate the harmonic contribution along with the use of an innovative automatic impact device to control the periodicity of the data triggering, signifying data flow at predefined block size. A formula was proposed to synchronize the impact and harmonic frequencies, thus ensuring successful elimination of the later. A decimal part of 0.5 within the impact frequency (representing 180 degrees phase difference between incoming blocks) demonstrated much efficient combination in removing the harmonic frequency in comparison to other values. In contrast, a triggering frequency magnitude that contained only a natural part produced insignificant elimination progress. Experiment conducted on a Fault Simulation Rig (FSR) showed that the dynamic characteristics of the structure of under the proposed operational EMA revealed close agreement with the classical EMA run under non-operational mode. The 1st and 2nd natural frequencies of non-operational condition, (10.9 Hz and 18.4 Hz) were slightly shifted to lower frequency (9.9 Hz and 17.6 Hz) under operational condition. Moreover, modal damping of the first two modes changed from 5.25% and 2.88% to 5.32% and 3.21%, respectively. Mode shapes for both non-operational and operational conditions remained highly similar, with pitching and heaving as the dominant mode shapes. The proposed method executed when the machine is running at superimposed frequency of the structure (i.e. 10 Hz) required 9623 impacts to enable block averaging to reach threshold coherence of more than 0.75. It was indicated that the differences of resonance frequencies and modal damping between both static and operational conditions was associated to the boundary condition of the machine structure that was not rigidly supported. The proposed EMA system applied under operational condition by utilizing a periodic control input force and time based block averaging algorithm can serve as added feature within the current machine maintenance protocols to ensure reliable diagnostic which will overcome unscheduled shutdown.